Mind-body exercise improves cognitive function and modulates the function and structure of the hippocampus and anterior cingulate cortex in patients with mild cognitive impairment - Tao, Jing (Neuroimage Clin, 2019)
Mild cognitive impairment (MCI) is a common neurological disorder. This study aims to investigate the modulation effect of Baduanjin (a popular mind-body exercise) on MCI. 69 patients were randomized to Baduanjin, brisk walking, or an education control group for 24 weeks. The Montreal Cognitive Assessment (MoCA) and Magnetic Resonance Imaging scans were applied at baseline and at the end of the experiment. Compared to the brisk walking and control groups, the Baduanjin group experienced significantly increased MoCA scores. Amplitude of low-frequency fluctuations (ALFF) analysis showed significantly decreased ALFF values in the right hippocampus (classic low-freqency band, 0.01‐0.08 Hz) in the Baduanjin group compared to the brisk walking group and increased ALFF values in the bilateral anterior cingulate cortex (ACC, slow-5 band, 0.01-0.027 Hz) in the Baduanjin group compared to the control group. Further, ALFF value changes in the right hippocampus and bilateral ACC were significantly associated with corresponding MoCA score changes across all groups. We also found increased gray matter volume in the Baduanjin group in the right hippocampus compared to the brisk walking group and in the bilateral ACC compared to the control group. In addition, there was an increased resting state functional connectivity between the hippocampus and right angular gyrus in the Baduanjin group compared to the control group. Our results demonstrate the potential of Baduanjin for the treatment of MCI.